Cognitive and neuroimaging profile of a Brazilian family with CADASIL - Júlio César Vasconcelos da Silva; Emerson L. Gasparetto; Charles André (Arquivos de Neuro-Psiquiatria)
Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is an inherited small vessel disease leading to small infarcts and subcortical vascular dementia. This study presents results from the neuropsychological and neuroimaging evaluation of functionally autonomous individuals of a Brazilian family with CADASIL. The causal mutation was confirmed in four family members. Seven individuals from two generations were evaluated using the CERAD battery and additional neuropsychological tests and were submitted (6 individuals) to magnetic resonance imaging (MRI) of the brain with specific protocols for white matter lesion quantification. Apraxic changes and fast progression over nine months (neuropsychological reevaluation of 6 individuals) were found in many individuals. The MRI study suggests greater involvement of frontal lobes in more severely affected individuals. Even functionally independent individuals may exhibit significant neuropsychological and neuroimaging changes. Apraxia, little commented on in literature, and rapidly progressive cognitive changes were found in this group.